Inconsistent associations between sweet drink intake and 2‐year change in BMI among Victorian children and adolescents. Issue 4 (19th June 2013) - Jensen, B. W.; Nichols, M.; Allender, S.; de Silva‐Sanigorski, A.; Millar, L.; Kremer, P.; Lacy, K.; Swinburn, B.
Summary: What is already known about this subject: Sugar‐sweetened beverages have been suggested as a possible contributor to the development of obesity. However, longitudinal evidence is limited, and most previous studies were conducted in the United States. It is unclear if the results are applicable to other parts of the world. What this study adds: We assessed the longitudinal association between sweet drink intake and body mass index in a large sample of children and adolescents in the Australian state of Victoria. We generally found limited evidence for a longitudinal association between various indicators of sweet drink consumption and body mass index. Objective: The aim of this study was to examine whether baseline (T1) or 2‐year change in sweet drink intake in children and adolescents was associated with age‐ and gender‐standardized body mass index (BMIz) at time two (T2), 2 years later. Methods: Data on 1465 children and adolescents from the comparison groups of two quasi‐experimental intervention studies from Victoria, Australia were analysed. At two time points between 2003 and 2008 (mean interval: 2.2 years) height and weight were measured and sweet drink consumption (soft drink and fruit juice/cordial) was assessed. Results: No association was observed between T1 sweet drink intake and BMIz at T2 among children or adolescents. Children from higher socioeconomic status families who reported an increased intake of sweet drinks at T2 compared with T1 had higher mean BMIz at T2 (β: 0.13, P = 0.05). There was no evidence of a dose–response relationship between sweet drink intake and BMIz. In supplementary analyses, we observed that more frequent usual consumption of fruit juice/cordial was associated with a higher BMIz at T2 among children. Conclusion: This study showed limited evidence of an association between sweet drink intake and BMIz. However, the association is complex and may be confounded by both dietary and activity behaviours.